COBERTURA INFORMATIVA EN EL PERIODISMO DIGITAL Y SU INCIDENCIA EN LA PERCEPCIÓN NOTICIOSA DE LOS CIUDADANOS DEL CANTÓN MIRA, AÑO 2024. - Herreria Recalde, Carlos Lonpio (2024)
This research was based on collecting and analyzing computer coverage in digital journalism and its impact on the news perception of citizens of the Mira canton, Carchi province. Focusing mainly on third-year high school students, during the year 2024. Therefore, surveys with 10 closed questions were applied in five educational institutions in the Mira canton, which provided us with a total of responses acquired from 304 students. A quantitative approach was used, allowing access to the corresponding statistics and tabulations of the analysis. The total percentage from the responses of the surveyed students specifically allowed us to identify the trends in digital news coverage carried out in the Mira canton. This analysis generated correct information on how students perceive and interpret news information within their social circle. The results emphasized the importance of the digital information system and the need to improve information data on the different platforms where news is posted, in addition, students in the face of false information. Through this study, above all, we generate a solid basis for recommendations aimed at promoting a more committed consumption of digital information.